2005
DOI: 10.1104/pp.104.054221
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Complementation. Map-Based Cloning in Chlamydomonas reinhardtii    

Abstract: Chlamydomonas reinhardtii is an excellent model system for plant biologists because of its ease of manipulation, facile genetics, and the ability to transform the nuclear, chloroplast, and mitochondrial genomes. Numerous forward genetics studies have been performed in Chlamydomonas, in many cases to elucidate the regulation of photosynthesis. One of the resultant challenges is moving from mutant phenotype to the gene mutation causing that phenotype. To date, complementation has been the primary method for gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 45 publications
1
71
0
1
Order By: Relevance
“…A dCAPS marker is made for each BAC gene to be tested in the transformant (Figure 1). Markers predicted by Rymarquis et al (2005) are tested. If no predictions are available, 39-UTR sequences are amplified and tested with 3-10 restriction enzymes (Bowers et al 2003).…”
Section: Methodsmentioning
confidence: 99%
“…A dCAPS marker is made for each BAC gene to be tested in the transformant (Figure 1). Markers predicted by Rymarquis et al (2005) are tested. If no predictions are available, 39-UTR sequences are amplified and tested with 3-10 restriction enzymes (Bowers et al 2003).…”
Section: Methodsmentioning
confidence: 99%
“…We chose 40 individuals as an ideal bulk size because, as discussed in section 3.2, this is the minimum number required to establish linkage if 25% recombination is observed (95% confidence level, Chi square). Although we could have analyzed only the albino class, which would be the norm for bulked segregant analysis in diploid organisms (Martinez-Morales et al, 2004;Michelmore et al, 1991;Rawls et al, 2003;Rymarquis et al, 2005), we also included the wild-type class for confirmation, and a 1:1 mix of the two pooled DNA samples as a control. In retrospect, the value of these extra samples in terms of increased confidence in the scoring far outweighs the modest increase in workload.…”
Section: Efficacy Of Bulked Segregant Analysis For Genetic Mappingmentioning
confidence: 99%
“…These results suggested that the APM1 and APM2 gene products may have physical interactions or that the genes may function in the same process or structure. With the completion of the Chlamydomonas molecular map (Kathir et al 2003;Rymarquis et al 2005) and the sequence of the nuclear genome (Merchant et al 2007), we were able to determine that apm1 mutations are caused by lesions in the DNAJ1 gene encoding the cytosolic Hsp40 type I protein, while the genetically interacting apm2 mutations are in the gene encoding cytosolic Hsp70A. The results indicate a previously unsuspected role of the Hsp70 chaperone system in regulation of microtubule stability.…”
mentioning
confidence: 55%